Cellulosics exhibition display (circa 1945) - Hercules Incorporated (1945)
Two close-up views of an exhibition display panel for cellulose products manufactured and sold by the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hercules Incorporated; Corporations; Chemical industry; Trade shows; Advertising; Advertising, Industrial; Plastics; Plastics industry and trade; Cellulose